Análise do escoamento superficial no alto curso da bacia hidrográfica do Rio Anil em São Luís - MA - Cruz, Walefe Lopes da (2022)
The present work aimed to analyze the surface runoff in the upper course of the Anil river basin, located in the city of São Luís/MA, with an area of 9.07 km². The specific objectives were: to assess land use and land cover; to physiographically characterize the upper course of the basin; identify the Curve Number of the area through the analysis of physiographic and climatological data of the area; identify the surface runoff of the area; and compare and validate this data through infiltration tests. To achieve these objectives, two research stages were carried out, namely, desk work and field work. In the first stage, activities were carried out for research planning, elaboration of maps, bibliographic analysis and writing of the text. In the second stage, fieldwork was carried out to get to know the area, take photographic records and carry out infiltration tests. After this stage, returning to the cabinet stage, graphs of the data obtained from the infiltration tests were prepared and the statistical analysis of the data generated with the tests was performed. 40 tests were carried out to obtain the values of accumulated infiltration, which were used as potential for water storage in the soil (S). The Curve Number (CN) technique was used, and surface runoff was estimated for the upper course with the aforementioned technique and infiltration tests. The data indicated that the runoff rates are lower than those identified with the infiltration test in vegetated areas and with exposed soil. The values obtained with the infiltration tests range from 24.2mm to 89.89mm for hydrological group B in vegetated areas and from 0 to 121.88mm in areas of exposed soil. The values of surface runoff in the same vegetated areas and with exposed soil obtained with the CN technique were, respectively, 42.45mm and 116mm. Regarding hydrological type D, the rates identified were from 2.55mm to 74.33mm for vegetated area and from 12.48mm to 100.8mm for areas with exposed soil. From the CN technique, the data generated for the same hydrological type D were 77.22mm and 107.7mm respectively. The tests with the highest runoff rates generated were respectively 14, 17, 20, 29 and 40, which were located in areas with exposed soil with CN ranging from 78 to 95, obtaining values greater than 100mm for precipitation of 139.4mm. The statistical analysis performed using the Spearman Correlation Matrix indicated that there is a very weak positive correlation between the surface runoff data generated by the CN technique and the infiltration tests carried out in vegetated areas and with exposed soil, generating a value of 0.037.